Pendampingan Pembuatan Key Performance Indicator Sebagai Perencanaan Program Kerja Tahunan dan Multi Tahun Berbasis Balance Score Card Pada Unit Pelaksana Teknis Daerah Balai Latihan Kerja (UPTD BLK) Disnakertransos Kabupaten Tulungagung - Cahyoadi, Bayu; Djatmiko, Andreas Andre (Universitas Nusantara PGRI Kediri, 2019)
Regional Technical Implementation Units (UPTD) Work Training Centers (BLK) and Regional Revenue Bodies (Bapenda) Disnakertrans Tulungagung Regency is a newly established public organization. As a new public sector, an institution should have maturity in the fields of management and organization that are reflected in measurable work plans, regulations, clear governance, standard operation procedures, and guarantees of quality quality of institutions and graduates who must always be evaluated with appropriate instruments. This program takes one of the above BCS perspectives, namely the internal business perspective; from the perspective of a strategy based on Human Resources (HR). The making of the BSC will be based on the details of the governance that has been determined by the laws and regulations related to the two UPTDs which are then determined by the indicators of the implementation of the work program based on the capacity of the HR they have. The making of the work program indicator is based on the key performance indicator (KPI) theory. The aim of the program and the benefits of this program is to become one of the proofs of good cooperation between the institutions of STKIP PGRI Tulungagung and the Regency Government of Tulungagung Regency especially at the UPTD BLK and Bapenda Disnakertrans; to donate lecturers' knowledge to the public; and to improve the quality of management of government / public sector management in the Tulungagung Regency area. While the benefits generated from this program are the creation of good cooperation between higher education institutions and the government; the creation of management management that refers to relevant scientific theory; the creation of high management management standards in government institutions, especially the BLK UPTD and the Bapenda Disnakertrans Tulungagung district.